2000
DOI: 10.4319/lo.2000.45.1.0044
|View full text |Cite
|
Sign up to set email alerts
|

Feeding selectivity and egg production of Calanus helgolandicus in the English Channel

Abstract: Copepods are able to discriminate between different foods on the basis of particle size and nutritional quality. However, the extent of selective feeding behavior and the mechanisms controlling it in the field are still poorly understood. In this study, we investigated selective feeding behavior and egg production for Calanus helgolandicus feeding on natural phytoplankton (using high-performance liquid chromatography techniques), and egg production, at a coastal station off Plymouth with the annual phytoplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 44 publications
3
105
1
1
Order By: Relevance
“…Some experimental studies have shown that cell size seems to be the main selection factor for C. finmarchicus and C. helgolandicus when feeding on algal cells with no clear distinction in external morphology (MEYER et al, 2002). However, a slight preference particularly for diatoms has been observed in the field for both species, although there has been little evidence developed for selective feeding on different phytoplankton (MEYER-HARMS et al, 1999;IRIGOIEN et al, 2000). In our study, C. australis exhibited a more carnivorous diet than D. forcipatus.…”
Section: Dietmentioning
confidence: 49%
“…Some experimental studies have shown that cell size seems to be the main selection factor for C. finmarchicus and C. helgolandicus when feeding on algal cells with no clear distinction in external morphology (MEYER et al, 2002). However, a slight preference particularly for diatoms has been observed in the field for both species, although there has been little evidence developed for selective feeding on different phytoplankton (MEYER-HARMS et al, 1999;IRIGOIEN et al, 2000). In our study, C. australis exhibited a more carnivorous diet than D. forcipatus.…”
Section: Dietmentioning
confidence: 49%
“…A recent study assessing the impacts of P. minimum on A. tonsa stated the insufficiency of this species as a food source, but did not report toxic effects (Dam and Colin 2005). An adverse effect of dinoflagellates on copepod egg production has been reported for Calanus helgolandicus in the field (Irigoien et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the Mediterranean Sea illustrate deleterious effects of diatoms on copepod reproduction (Miralto et al 1999) and depression of reproductive success at high Thalassiosira abundance has been reported for Calanus pacificus from Dabob Bay, Washington (Pierson et al 2005). Yet, other work provides evidence for the importance of diatoms as copepod food (Irigoien et al 2002), and grazing selectivity in favour of diatoms has been demonstrated in copepods under natural conditions (Meyer-Harms et al 1999;Irigoien et al 2000). The diatom Thalassiosira weissflogii has been proved to constitute a high-quality food source for copepod development (Klein Breteler et al 2005), including Acartia tonsa (Støttrup and Jensen 1990;Jónasdottir and Kiørboe 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The application of the CHEMTAX program to pigment data from phytoplankton samples has been shown to be a useful tool in marine environments for several purposes, including medium-large scale analysis of phytoplankton class distribution in the open ocean (Schlüter et al 2000;Wright and Van der Enden 2000;Vidussi et al 2000;Higgins and Mackey 2000;Gibb et al 2001;Latasa et al 2005) and zooplankton feeding studies (Irigoien et al 2000;Guisande et al 2002). However, the application of CHEMTAX in freshwater environments has received little attention (Buchaca et al 2004;Fietz and Nicklisch 2004;Descy et al 2005;Schlüter et al 2006).…”
Section: Introductionmentioning
confidence: 99%